The effects of fresh Gastrodia elata Blume on the cognitive deficits induced by chronic restraint stress - Huang, Hong; Zhang, Yiwen; Yao, Caihong; He, Qinghu; Chen, Fang; Yu, Han; Lu, Guanghua; Jiang, Ning; Liu, Xinmin (Frontiers in Pharmacology, 2022)
Chronic restraint stress (CRS) is a classic animal model of stress that can lead to various physiological and psychological dysfunctions, including systemic neuroinflammation and memory deficits. Fresh Gastrodia elata Blume (FG), the unprocessed raw tuber of Gastrodia elata Blume, has been reported to alleviate the symptom of headache, convulsions and neurodegenerative diseases, while the protective effects of FG on CRS-induced cognitive deficits remains unclear. This work aimed to evaluate the effects of FG on CRS-induced cognitive deficits through multiplex animal behavior tests and to further explore the related mechanism by observing the expression of mitochondria apoptosis related proteins in mouse hippocampus. In in vivo experiments, mice were subjected to object location recognition test (OLRT), new object recognition test (NORT), Morris water maze test (MWMT) and passive avoidance test (PAT) to evaluate the learning and memory ability. In in vitro experiments, the expression of AKT/CREB pathway, the fission and apoptosis related proteins (Drp1, Cyt C, BAX) as well as the pro‐inflammatory cytokines (TNF‐α and IL‐1β) level in hippocampus was examined. Our results demonstrated that in the spontaneous behavior experiments, FG significantly improved the cognitive performance of CRS model mice in OLRT (P < 0.05) and NORT (P < 0.05). In the punitive behavior experiments, FG shortened the escape latency in long-term spatial memory test (MWMT, P < 0.01), and prolonged the latency into the dark chamber in non-spatial memory test (PAT, P < 0.01). Biochemical analysis showed that FG treatment significantly suppressed CRS‐induced Cyt C, Drp1 and BAX activation (P < 0.001, P < 0.01 and P < 0.05), promoted CREB, p-CREB, AKT and p-AKT level (P < 0.05, P < 0.01 and P < 0.001), as well as inhibiting CRS‐induced pro‐inflammatory cytokines (TNF‐α and IL‐1β, P < 0.05 and P < 0.001) level in the hippocampus. Taken together, these results suggested that FG could attenuate cognitive deficits induced by CRS on multiple learning and memory behavioral tests.